Blood-Based Biomarkers for Metabolic Syndrome. (June 2016) - O'Neill, Sadhbh; Bohl, Mette; Gregersen, Soren; Hermansen, Kjeld; O'Driscoll, Lorraine
Abstract : Metabolic syndrome (MetS) is a constellation of factors increasing the risk of type 2 diabetes mellitus (T2DM), cardiovascular disease (CVD), and cancer. MetS diagnosis is cumbersome and the precise diagnosis differs throughout the world. Efforts are underway to find MetS biomarkers that could all be analysed in a single blood sample. Here we review recent advances, including progress on circulating exosomes and microvesicles and their molecular contents, as well as DNA, RNAs, and proteins taken directly from blood samples. While additional research is now warranted to advance upon these findings, there is reason for optimising that such blood-based entities will be beneficial for MetS diagnosis and will help reduce risk of T2DM, CVD, and cancers, contributing both societal and economic benefit. Trends: Metabolic syndrome (MetS) causes substantial morbidity and increases the risk of developing type 2 diabetes mellitus, cardiovascular disease, and cancer. MetS diagnosis is cumbersome and so MetS often goes unnoticed and untreated. Early diagnosis might enable early intervention, appropriate and timely MetS management, potentially preventing the development of more serious pathologies, and increasing quality-of-life and longevity. Minimally invasive biomarkers for MetS diagnosis and, ultimately, for screening those at risk of developing MetS that could be analysed from one blood sample would be of substantial benefit to reducing this problem. Recent advances in this field suggest that extracellular vesicles and their molecular contents, as well as DNA, RNAs, and proteins taken directly from blood samples might be used as biomarkers to diagnose MetS.